(untitled) (Journal of Face Aesthetics, 2021)
Skin is the organ in permanent contact with environmental factors which could accelerate the aging process. The changes occurring due to the aging process are particularly noticeable in the skin. Skin ageing is dependent on endogenous and exogenous factors determined by environmental factors, primarily the ultraviolet radiation (photoaging). The Authors reviewed the articles available at PubMed, ResearchGate and GoogleScholar on the composition and application of preparations containing snail mucus. The results of the literature analysis revealed that snail mucus contains substances such as allantoin, glycolic acid, lactic acid, collagen, elastin, extracellular matrix metalloproteinases as well as their inhibitors, and antioxidant enzymes. Also, it was demonstrated that the use of preparations containing snail mucus had beneficial effects on the condition of the skin, including improved skin hydration, normalisation of the thickness of the epidermis, improved skin structure, increased cell proliferation index, reduction of skin elastosis and decreased hyperpigmentation. Moreover, the regenerative mechanism of action of snail mucus resulted in a clinical alleviation of lesions in patients with dermatological problems of various aetiology. Therefore, it appears that snail mucus could be a good biostimulator and its use has many beneficial effects for the skin.